The Marvi Madrasa and its Developments During the Qajar Period - Maryam Heydarkhani; Zahra Ahari (صفه)
Marvi Madrasa was one of the most important madrasas in the Qajar period built by Mohammad Hossein Khan-e Marvi, a high-ranking person in the Fath-Ali Shah court, in a period of the rising importance of educational and religious institutions in tandem with the rising influence of religious scholars (Ulama). The purpose of this paper is to study the spaces and activities of the madrasa at its beginning as an educational institution, and its subsequent changes due its changing social status during the Qajar. Employing a historical method, primary sources, especially endowments, and Qajarid maps have been studied, and exploring the physical composition of the madrasa, its changes have been interpreted.From its beginning, the madrasa contained spaces of various functions such as mosque, bathhouse, icehouse, and elementary school (maktabkhana), built for education and everyday life of the students (talabas). In a short time, the madrasa became a first-rated educational centre in Tehran. By building a bazaar and transforming its path to a 'street', the madrasa found its local and urban center, and the setting was prepared for its spatial expansion. The expansion of the 'mosque' was a turning point in the life of the madrasa. Located besides the 'madrasa' it became the main space. Public religious activities became significant and the madrasa became a powerful socio-religious centre. With spatial developments around the madrasa and the change of social and political situation, the madrasa found an important role in the Constitutional events and the madrasa became a point of contention between the government and the ulama over its tutelage. At the end of the Qajar period, and with the spread of intellectual views and new schools, the madrasa declined and its spatial scope changed. During this period, the spaces, activities, people, and social role of the madrasa underwent changes, and despite the 'madrasa' being initially the main space of the complex, at the end of the Qajar period, it was the combination of the 'mosque' and the 'madrasa' that formed the life of the complex.